2014
DOI: 10.1007/s12253-014-9863-x
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Oncological Outcome After Abdominoperineal Resection or Low Anterior Resection for Lower Rectal Cancer

Abstract: In lower rectal cancer, postoperative outcome is still subject of controversy between the advocates of abdominoperineal resection (APR) and low anterior resection (LAR). Reports suggest that low anterior resection may be oncologically superior to abdominoperineal excision, although no good evidence exists to support this. Publications were identified which assessed the differences comparing 5-year survival, local recurrence, circumferential resection margin rate, complications and so on. A meta-analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 25 publications
4
33
0
4
Order By: Relevance
“…At pathology, all cases were evaluated as no ink on the tumor. These results are positive compared with the literature, where approximately 15% to 30% positive resection margins are reported in these challenging cases …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…At pathology, all cases were evaluated as no ink on the tumor. These results are positive compared with the literature, where approximately 15% to 30% positive resection margins are reported in these challenging cases …”
Section: Discussionsupporting
confidence: 53%
“…[14][15][16] In the current study, only one out of are reported in these challenging cases. 17,18 Of the 36 lymph node targets, which were all located outside the mesorectum, 33 were successfully removed. The three missed lymph node targets were all located at the obturator region, and their size was decreased to 3, 3, and 5 mm due to neoadjuvant CRT.…”
Section: Discussionmentioning
confidence: 99%
“…The object is to achieve a tumour‐free circumferential resection margin (CRM) to reduce the risk of local recurrence . Patients with low rectal tumours requiring an abdominoperineal excision (APE) may have a poor prognosis . The operation is associated with higher rates of CRM involvement, tumour perforation and incomplete surgical removal compared with anterior resection for more superiorly located rectal tumours .…”
Section: Introductionmentioning
confidence: 99%
“…Low rectal cancer is a challenging disease, particularly when the tumor invades the anal sphincter complex (ASC). These tumors are typically removed by an abdominoperineal excision (APE), although patients requiring this type of surgery end up with a permanent colostomy and have a poorer oncological outcome compared to anterior resection (Wang et al, ). Damage to the anal sphincters, iatrogenic tumor perforation and incomplete tumor resection are frequently encountered and related to increased local recurrence and decreased survival (den Dulk et al, ).…”
Section: Introductionmentioning
confidence: 99%